Enhancing tool life with the development of silicon nitride based inserts for high speed machining of Inconel 718 using hybrid microwave sintering - Ariff, Tasnim Firdaus; Azhar, Ahmad Zahirani; Bahar, Rubina; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul (2018)
Hybrid Microwave (HMW) sintering is becoming popular for heating ceramics, composites, metals and alloys. It is becoming a trendy research due to its capabilities in saving time, energy and money, increasing efficiency and productivity, improving mechanical and structural properties. Silicon Nitride (Si3N4) is widely used as a cutting insert for machining cast iron, hard steel and nickel based alloys. It is mass produced by traditional powder technology. This research aims to increase the tool life of the Silicon Nitride inserts by enhancing the mechanical and structural properties by using Hot Isostatic Pressing (HIP) at 1800°C and followed by hybrid microwave (HMW) post-sintering at 200°C for 10 minutes with the aid of Silicon Carbide powder as susceptor. Three different compositions (88%, 90% and 92% Si3N4) were synthesized in order to find the optimum composition using these techniques. Mechanical and structural properties were analyzed. The combination of HIP+HMW post sintering for just 10 minutes significantly enhanced the density (93-97%TD), hardness (18-22%), compressive strength (2-4%) and produced finer uniform grains particularly for 88% and 90% Si3N4 when compared with HIP samples without any post sintering effect. Hence, the 88% and 90% Si3N4 compositions produced by the combination of HIP+HMW post sintering are potentially suitable candidates for machining hard materials such as Inconel 718. The effect of different susceptors on the tool life of various Si3N4 inserts (90Si3N4 4Y2O3 2.5MgO 2Al2O3 1.5SiO) that have been synthesized in machining Inconel 718. The Si3N4 inserts have been synthesized by means of Hot Isostatic Pressing (HIP) at 1800°C and followed by Hybrid Microwave (HMW) post-sintering at 200°C for 10 minutes with the aid of three different susceptors; Silicon Carbide (SiC), Graphite (G) and mixture of (SiC + G) powders. HMW post sintering for only 10 minutes using SiC, G and SiC+G susceptors enhanced the density (97-98%TD) and hardness (27-58%) significantly. Finer uniform grains and less porosities were produced particularly for Si3N4 inserts produced by HMW (SiC+G) when compared with HMW (SiC) and HMW (G). Tool life for the Si3N4 inserts were improved by 10-17% HMW(SiC), 20-53 % HMW(G) and 32-88% HMW(SiC+G) for the cutting speeds of 100, 125 and 160 m/min. Hence, the mixture of SiC +G powders as susceptors produced the best outcome for Si3N4 inserts with enhanced densification, hardness, wear resistance, and longer tool life (88% increment at 100 m/min) when compared with the commercial tool (RNGN 6060) in machining Inconel 718.